Treatment and clinical outcome of needle-track seeding from hepatocellular carcinoma - Ahn, Dong-Won (The Korean Association for the Study of the Liver, 2011)
BACKGROUND/AIMS: Needle-track seeding is a rare but important complication of diagnostic and therapeutic ultrasound (US)-guided procedures in hepatocellular carcinoma (HCC). We examined the frequency of needle-track seeding after US-guided percutaneous ethanol injection (PEI), fine-needle aspiration biopsy (FNAB), and percutaneous transhepatic biliary drainage (PTBD) in order to determine the appropriate treatment for needle-track seeding and its clinical outcome. METHODS: We analyzed the clinical characteristics and treatment outcomes in eight patients who experienced needle-track seeding from HCC after an US-guided procedure (FNAB, PEI, or PTBD) between January 1990 and July 2004. RESULTS: Seven (0.14%) of 5,092 patients who experienced needle-track seeding (2 after PEI, 4 after FNAB, and 1 after PTBD) during the study period and 1 other patient who experienced needle-track seeding recently were recruited for this study. Two of the eight patients underwent mass excision and the other six patients underwent en-bloc wide excision for the needle-track seeding. Tumors recurred in the needle-tracks in both patients who underwent mass excision but not in the six patients who underwent en-bloc wide excision. Mortality occurred in three patients who experienced the recurrence and progression of intrahepatic HCC. CONCLUSIONS: The incidence of needle-track seeding after US-guided procedures in HCC was 0.14%. En-bloc wide excision seems to be the optimal treatment for minimizing the probability of tumor recurrence due to needle-track seeding.